Effects of light intensity on the growth of Polygala fallax Hemsl. (Polygalaceae) - Liang, Huiling; Liu, Baoyu; Wu, Chao; Zhang, Xiujiao; Wang, Manlian; Huang, Xiyang; Wan, Li; Tang, Hui (Frontiers in Plant Science, 2022)
Polygala fallax Hemsl. (Polygalaceae), a traditional Chinese medicinal species, requires optimal growth conditions for artificial cultivation. Irradiance is one of the primary environmental factors that affects the growth and survival of P. fallax Hemsl. plants, which seemingly grow better under weak irradiance conditions. However, the optimum light intensity for growing P. fallax Hemsl. is not clear. To determine the optimum light intensity for cultivating this medicinal plant species, P. fallax Hemsl. plants from two different habitats were grown and exposed to three shade treatments (50% shade, 70% shade and 90% shade, which resulted in photosynthetically active radiation amounts equal to 662 μmol m−2 s−1, 401 μmol m−2 s−1, and 131 μmol m−2 s−1, respectively) to evaluate survival, growth, leaf photosynthesis, and the main pharmacological active ingredients (saponins) in response to shade. Our results revealed that the P. fallax Hemsl. plants in the different habitats consistently exhibited relatively high photosynthesis rates, biomass, survival rates and saponins under 662 μmol m−2 s−1 created by the 50% shade treatment. We concluded that photosynthetically active radiation of approximately 662 μmol m−2 s−1 is suitable for the cultivation of P. fallax Hemsl. plants.